2021
DOI: 10.1038/s41398-021-01428-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gut microbiome in mice model of depression with divergent response to escitalopram treatment

Abstract: Depression is a common and heterogeneous mental disorder. Although several antidepressants are available to treat the patients with depression, the factors which could affect and predict the treatment response remain unclear. Here, we characterize the longitudinal changes of microbial composition and function during escitalopram treatment in chronic unpredictable mild stress (CUMS) mice model of depression based on 16 S rRNA sequencing and metabolomics. Consequently, we found that escitalopram (ESC) administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 43 publications
2
32
1
Order By: Relevance
“…Potent anti-inflammatory properties have also been reported in this context ( Baxter et al., 2019 ). Muribaculaceae and associated coproduced short-chain fatty acids have been significantly correlated with depression ( Duan et al., 2021 ), but there is no direct evidence to prove the relevant brain mechanism in MDD. Currently, inosine is commonly used in the treatment of Parkinson’s disease ( Schwarzschild et al., 2014 ) and multiple sclerosis ( Markowitz et al., 2009 ), and it has exhibited direct anti-inflammatory effects on pleural inflammation ( da Rocha Lapa et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potent anti-inflammatory properties have also been reported in this context ( Baxter et al., 2019 ). Muribaculaceae and associated coproduced short-chain fatty acids have been significantly correlated with depression ( Duan et al., 2021 ), but there is no direct evidence to prove the relevant brain mechanism in MDD. Currently, inosine is commonly used in the treatment of Parkinson’s disease ( Schwarzschild et al., 2014 ) and multiple sclerosis ( Markowitz et al., 2009 ), and it has exhibited direct anti-inflammatory effects on pleural inflammation ( da Rocha Lapa et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potent anti-inflammatory properties have also been reported in this context (Baxter et al, 2019). Muribaculaceae and associated coproduced short-chain fatty acids have been significantly correlated with depression (Duan et al, 2021), but there is no direct evidence to prove the relevant brain mechanism in MDD. Currently, inosine is commonly used in the treatment of Parkinson's The mutual discriminative KEGG pathways among three groups representing in CUMS+saline and CUMS+inosine groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the animal studies of stress and depression covered in this review, most studies reported that stress increased Firmicutes abundance, however Bacteroidetes abundance was more variable (Table 1). Interestingly, Duan et al [104] showed Firmicutes abundance was higher, and Bacteroidetes abundance was lower in mice which did not respond to Escitalopram antidepressant treatment than those that did respond to treatment. Given that the causes of treatment resistance in up to 30% of depressive patients remain elusive, future studies of gut microbiota disturbances in non-responders are warranted [105].…”
Section: Gut Microbial Compositionmentioning
confidence: 99%
“…Actinobacteria and Proteobacteria have been shown to be altered in depressive patients compared to healthy individuals [5,14], however in animal models of stress and depression alterations in these two phyla were inconsistent (Table 1). Increased [34,42,52,54,108] Increased [21,108] Cecum [51,106] Decreased [63,95,104,[107][108][109] Decreased [42,51,52,54,64,68] Decreased [104] Decreased [42] Faecal pellets [21,42,52,54,63,64,68,95,103,104,[107][108][109][110] No change [110] No change [103,106,110] -No change [54] CRS -Increased [69,98,…”
Section: Gut Microbial Compositionmentioning
confidence: 99%
“…Accumulating evidence suggests that gut microbiota is involved in the pathogenesis of depression ( Bai et al., 2021a ; Bai et al., 2021b ; Liu L. et al., 2021 ). Animal studies have shown the reproducible and consistent effects of gut microbiota on mouse behavior through inflammation ( Farag et al., 2020 ; Duan et al., 2021 ; Dordević et al., 2021 ; Zhang C. et al., 2021 ). Our group recently observed that CD36 deficiency could affect depressive-like behaviors possibly by modifying gut microbiota compositions in mice ( Bai et al., 2021a ); and gut microbiota-related metabolites held the promise as potential biomarkers for diagnosing depression ( Bai et al., 2021b ).…”
Section: Introductionmentioning
confidence: 99%